Bond-based peridynamics for quasi-brittle materials - Mohd Hilmy Naim, Mohd Yakin (2024)
Accurately predicting fracture initiation and propagation in quasi-brittle materials is paramount for ensuring the safety and reliability of engineering structures. This study aims to address this challenge by validating an in-house MATLAB code based on the Bond-Based Peridynamics (BBPD) formulation, incorporating the Quasi-Brittle (QBR) damage model. Additionally, it examines the impact of integrating the QBR damage model and the Adaptive Dynamic Relaxation (ADR) technique within the BBPD frameworks and develops an innovative Adaptive Quasi-Brittle (AQBR) damage model for BBPD, integrating a material hardening parameter. The proposed methodology seeks to mitigate computational costs in Peridynamics simulations and enhance fracture modeling capabilities. Through numerical examples, the effectiveness of the proposed methodology is demonstrated, showcasing improved capabilities and reduced computational costs. The integration of ADR in QBR ensures good agreement with literature outcomes and mitigates the computational costs associated with explicit time integration methods during the analysis of quasi-static loading. Importantly, the introduction of the new developed AQBR damage model significantly reduces relative errors and surpasses the performance of QBR, laying the groundwork for further exploration of nonlinear damage models in fracture mechanics within the context of BBPD. This study’s methodology has broader implications for the field of fracture mechanics, offering a more robust and efficient approach to modeling fracture initiation and propagation in quasi-brittle materials within the framework of BBPD. The introduction of the AQBR model proves crucial, as evident in its capacity to reduce relative errors up to 20% when comparing force-displacement results with the existing literature, surpassing the performance of QBR. The inclusion of the AQBR damage model into BBPD marks a foundational step, laying the groundwork for further exploration of nonlinear damage models in fracture mechanics